Pengaruh Pertumbuhan Ekonomi, UMK, dan Tingkat Investasi terhadap Penyerapan Tenaga Kerja di Kabupaten dan Kota di Provinsi Jawa Tengah - Alam Reza Berlian; Nugroho Sumarjiyanto Benedictus Maria (Universitas Diponegoro, 2023)
This study analyzes the impact of economic growth, minimum wages at the district/city level, and foreign direct investment on labor absorption among the working-age population. The data used spans the period from 2017 to 2020 and covers 35 districts and cities in Central Java Province. The data analysis method employed is the Fixed Effects Model approach. Based on the analysis results, the variables of Gross Domestic Product and Foreign Direct Investment have a positive effect on labor absorption, while the variable of Minimum Wages at the district/city level has a negative effect on labor absorption.